Structure Mapping and Vocabularies for Thinking. (2nd June 2017) - Loewenstein, Jeffrey
Abstract: While extremes tend to capture attention, the ordinary is often most of the story. So it may be with the structure‐mapping process. The structure‐mapping process can account for such pinnacles of thinking as analogy and metaphor, which can lead to overlooking the mundane, incremental use of structure mapping. Consequently, the current discussion shifts focus to the value of close comparisons between literally similar items for the development of knowledge. The intent is to foster greater integration between process and content as well as between individuals and collectives. The payoff is identifying some undue simplifications and some promising new directions. Abstract : Close comparisons between literally similar items foster the development of knowledge. Emphasizing mundane close comparisons, as opposed to extraordinary distant analogies, helps to integrate discussions of process and content as well as discussions of individuals and of social collectives. The legacy of knowledge we generate, learn, use, and pass along to future generations is an achievement—an achievement that structure‐mapping theory helps explain.